Modelling and simulation for autonomous systems : 4th International Conference, MESAS 2017, Rome, Italy, October 24-26, 2017, Revised selected papers /: 4th International Conference, MESAS 2017, Rome, Italy, October 24-26, 2017, Revised selected papers. (2018) - Unknown
No abstract available